2015
DOI: 10.1242/dev.115329
|View full text |Cite|
|
Sign up to set email alerts
|

The transmembrane protein Crumbs displays complex dynamics during follicular morphogenesis and is regulated competitively by Moesin and aPKC

Abstract: There was an error published in Development 142, 1869-1878.On p. 1869, the sentence 'Recently, the JM domain was implicated in specifying the position of a supercellular actomyosin cable, by concentrating atypical protein kinase C (aPKC) away from the site of the cable, thereby allowing an increase in localized Rhomboid (Rho) activity (Roper, 2012).' should instead have read:'Recently, the JM domain was implicated in specifying the position of a supercellular actomyosin cable, by concentrating atypical protein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 60 publications
2
21
0
Order By: Relevance
“…Accordingly, CMs have been reported to exhibit substantial cellular plasticity during trabeculation, losing their cobblestone-like shape once they start delaminating (Liu et al, 2010;Staudt et al, 2014). Our observations are consistent with previous reports in Drosophila where during follicular morphogenesis as cells change shape, Crb is lost from the marginal zone (the most apical surface), relocalizes to the AJ and subsequently reappears at the marginal zone (Sherrard and Fehon, 2015;Wu et al, 2016). We found that blocking Nrg/ErbB2 signaling leads to relocalization of Crb2a from the junctions to the apical surface of CMs.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Accordingly, CMs have been reported to exhibit substantial cellular plasticity during trabeculation, losing their cobblestone-like shape once they start delaminating (Liu et al, 2010;Staudt et al, 2014). Our observations are consistent with previous reports in Drosophila where during follicular morphogenesis as cells change shape, Crb is lost from the marginal zone (the most apical surface), relocalizes to the AJ and subsequently reappears at the marginal zone (Sherrard and Fehon, 2015;Wu et al, 2016). We found that blocking Nrg/ErbB2 signaling leads to relocalization of Crb2a from the junctions to the apical surface of CMs.…”
Section: Discussionsupporting
confidence: 92%
“…We found that blocking Nrg/ErbB2 signaling leads to relocalization of Crb2a from the junctions to the apical surface of CMs. Interestingly, in Drosophila, depletion of cytoskeletal proteins required for Crb localization leads to relocalization of apical Crb to the junctions (Sherrard and Fehon, 2015). These data indicate that Crb2a localization is very dynamic and that Nrg/ErbB2 signaling, which is essential for cardiac trabeculation, is required for its junctional to apical shift.…”
Section: Discussionmentioning
confidence: 92%
“…Similarly, mutating Tyr10 in the FBM of the intercellular adhesion molecule (ICAM)-2 or the equivalent Tyr residue in the FBM of the neural cell adhesion molecule L1 impairs interaction with the FERM proteins radixin and ezrin, respectively ( Hamada et al, 2003 ; Cheng et al, 2005 ). Moreover, it has been shown recently that the FBM of Crb is necessary for organising D Moe, aPKC and the actin cytoskeleton at the marginal zone in the developing follicular epithelium ( Sherrard and Fehon, 2015 ). And in cervical carcinoma cells, over-expression of the mammalian CRB3 protein restores an epithelial-like morphology by organising a cortical actomyosin network through the regulation of the p114RhoGEF-RhoA-ROCK1/2 pathway via the FERM protein Ehm2 ( Loie et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…Crb and Sdt are required to stabilize epithelia (Grawe et al, 1996;Tepass, 1996;Bachmann et al, 2001;Hong et al, 2001;Campbell et al, 2009) and to negatively regulate actomyosin during tissue remodeling (Röper, 2012;Flores-Benitez and Knust, 2015). Consistent with this, changes in Crb protein levels, subcellular localization, and/or gene expression correlated with various epithelial remodeling events (Campbell et al, 2011;Röper, 2012;Sherrard and Fehon, 2015). Additionally, the crb and sdt genes encode multiple isoforms in Drosophila melanogaster.…”
Section: Introductionmentioning
confidence: 89%